2017
DOI: 10.1002/osp4.96
|View full text |Cite
|
Sign up to set email alerts
|

Distance learning strategies for weight management utilizing online social networks versus group phone conference call

Abstract: SummaryObjectiveThe increase in technology and online social networks (OSNs) may present healthcare providers with an innovative modality for delivering weight management programmes that could have an impact on health care at the population level. The objective of this study was to evaluate the feasibility and efficacy of using an OSN to deliver a weight loss programme to inform future, large‐scale trials.MethodsSeventy individuals (age = 47 ± 12.4, minority = 24.3%) with obesity (BMI = 36.2 ± 4.0) completed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
50
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(53 citation statements)
references
References 40 publications
0
50
0
3
Order By: Relevance
“…With regards to design, 4 studies were randomised control trials (RCTs) [ 26 29 ], 3 mixed methods [ 30 32 ], 3 non-controlled before-after trials (NCBA) [ 33 35 ], 5 controlled before-and-after trial (CBA) [ 36 40 ], and 3 cross-sectional [ 37 , 39 , 41 ]. Most of the papers were published between 2017 and 2020 (13 of 16) [ 26 35 , 37 , 40 , 41 ], and included the following social media platforms: Facebook, Instagram, Reddit, Twitter, and WeChat. Most data were collected within the USA (9 studies) [ 28 30 , 33 37 , 39 ], and 11 out of 18 studies targeted young adults aged between 18 and 35 years old [ 26 , 28 , 29 , 33 , 36 40 ] and eight included college/university students [ 28 , 33 , 36 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…With regards to design, 4 studies were randomised control trials (RCTs) [ 26 29 ], 3 mixed methods [ 30 32 ], 3 non-controlled before-after trials (NCBA) [ 33 35 ], 5 controlled before-and-after trial (CBA) [ 36 40 ], and 3 cross-sectional [ 37 , 39 , 41 ]. Most of the papers were published between 2017 and 2020 (13 of 16) [ 26 35 , 37 , 40 , 41 ], and included the following social media platforms: Facebook, Instagram, Reddit, Twitter, and WeChat. Most data were collected within the USA (9 studies) [ 28 30 , 33 37 , 39 ], and 11 out of 18 studies targeted young adults aged between 18 and 35 years old [ 26 , 28 , 29 , 33 , 36 40 ] and eight included college/university students [ 28 , 33 , 36 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Overweight participants lost 1–5 pounds and healthy weight participants lost 0.2 to 7 pounds (not statistically significant). Williams et al (2019) [ 35 ] USA N = 23 (100% Female) Mean Age = Not reported Ethnicity = Not reported Target Group = Primigravid women, ≥18 years of age, English or Spanish speaking, receiving care at clinic NCBA (Feasibility Study Pilot intervention) Anthropometric measures (height, weight, weight gain during pregnancy, postnatal weight loss, baby length/weight), nutrition and physical activity (pre-post surveys). Medium : Facebook Type of Social Media: Interaction and Information – Health messages were shared and interaction was promoted between the participants as well as with the health care worker.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations